(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The main objective of the research was to identify the level of Modern Technologies Application in Improving the Productivity of cows by cow Breeders in Duhok Governorate / Kurdistan Region-Iraq. The results of the research showed that the degrees of the application level of technologies ranged between (42-62), with an arithmetic mean of (51.71) degrees and a standard deviation of (6.09). It was found that the level of modern technologies application by cow breeders is low tends to medium. The results also showed that the technology ( Improving the nutritional value of the stored feed (increasing the storage period for the stored feed) (the use of antifungals and antioxidants in the stored feed) in the field of (technologies for the exploitation of fodder and feeding methods ) came first in terms of application with a mean of (2.44) and a standard deviation (0.67). While in the field of (techniques to improve genetic structures and increase offspring) the technology Selection of mothers with good genotype (females selected for the purpose of vaccination) came first in terms of application with a mean of (1.87) and a standard deviation (0.81). As for In the field of (Animal health care technologies) the technology (The use of diagnostic technology and early detection of diseases) came first with a mean (2.48) and a standard deviation (0.6). it was found that there is a significant correlation at the probability level (0.05) of the Years of experience in raising cows and annual income from raising cows while it was found that there is a significant correlation at the probability level (0.01) of the purpose of breeding, herd size, and communication with information sources on modern technologies. As for the obstacles facing cattle breeders in the field of applying modern technologies, the obstacle (The high costs of using modern technologies and market challenges) ranked first among (9) obstacles facing cow breeders